Manejo integrado de maleza en variedades de maní (Arachis hipogaea L.) - Cárdenas Icasa, Lidia Betty (2009)
The investigation was carried out in the Property The Cármen of property of Mrs. Cármen Icasa, located in the Km 17 of the road Quevedo - San Carlos, county of The Rivers. Located to an altitude of 280 msnm *, with a located western longitude of 79 25 W and south latitude of 1 05 S; he/she had as objective to evaluate the effect of the herbicides and cultural control of the overgrowths in two peanut varieties. For it was used it Totally at random the Design of Blocks (DBCA) with factorial arrangement of 2 x 3, with 6 repetitions and 8 experimental units; the Control of overgrowths was evaluated to the 30, 60 and 90 days, Days to floración to the 36 and 43 days, Number of sheaths for plant, seed Number for plant, Weight of 100 seeds, Yield in kg. for parcel. According to the results, one observes that the effect of the herbicides on the control of the overgrowths to the 30 days didn't show differences but to the 60 days the Treatment T2 (INIAP-380/Flex 1L/Ha-1 + Verdict 900ml/Ha-1), it showed difference with 83,33 and to the 90 days the result was shown similar in all the treatments, it is in the parameter from 70 to 89 good considered% in post-emergent application. The percentage of the days to the floración to those, 36 and 43 days didn't show statistical differences reaching an average to the 36 days the Treatment T6 (INIAP 381-Rosita/Testigo), of 75%; the Treatments T5 (INIAP 381-Rosita/Flex 1L/Ha-1 + Verdict 900ml/Ha-1) and Treatment T6 (INIAP 381-Rosita/Testigo); to the 43 days they presented 100% of flourished plants. In what refers to the number of sheaths for plant in the interaction of the Treatments, I present highly significant statistical differences being better the Treatment T1 (INIAP-380/Blazer 1L/Ha-1 + Verdict 900ml/Ha-1); with an average of 20.85 number of sheaths and the Treatment T5 (INIAP 381-Rosita/Flex 1L/Ha-1 + Verdict 900ml/Ha-1) and Treatment T6 (INIAP 381-Rosita/Testigo); with an average of 17.74 and 17.62 number of sheaths for plant. Regarding the number of seeds for plant didn't present statistical differences, being the Treatment T1 (INIAP-380/Blazer1L/Ha-1 + Verdict 900ml/Ha-1), with an average of 52,81 seed number for plant and the Treatment T6 (INIAP 381-Rosita/Testigo); with an average of 49,72 seeds for plant. For the weight of 100 seeds in the interaction of the treatments didn't present statistical differences, being the Treatment T1 (INIAP-380/Blazer 1L/Ha-1 + Verdict 900ml/Ha-1) who obtained the best weight in 52,33 g. and the Treatment T4 (INIAP 381-Rosita/Blazer 1L/Ha-1 + Verdict 900ml/Ha-1) who 35 g obtained. With regard to the yield reached in 123.12 m2. In the interaction of the treatments it showed statistical differences, the best treatment was the T1 (INIAP-380/Blazer 1L/Ha-1 + Verdict 900ml/Ha-1), with an average of 31.37 Kg. /5.76m2 followed by the T4 (INIAP 381-Rosita/Blazer 1L/Ha-1 + Verdict 900ml/Ha-1), with an average of 31,16 Kg/5.76m2. Giving a yield the Treatment T1 (INIAP-380/Blazer 1L/Ha-1 + Verdict 900ml/Ha-1), of 1520 grams in 5.76 m2, obtaining for hectare a yield of 2639 Kg. /Ha. and the Treatment T4 (INIAP 381-Rosita/Blazer 1L/Ha-1 + Verdict 900ml/Ha-1), with a yield of 1492 grams in 5,76 m2, giving for hectare 2590 Kg. /Ha. The smallest production cost obtained it however the treatments that were not applied herbicides considered witness, the profitability it is directly related to the costs, like to the production in Kg/Ha. that was obtained in each treatment, the T1 (INIAP-380/Blazer 1L/Ha-1 + Verdict 900ml/Ha-1) he/she obtained the biggest profitability 1.33% with a 1520 Kg. /5.76 m2. in front of -0,16% of the T4 (INIAP381-Rosita/Testigo) whose production was 1492 Kg. /5.76 m2. The hypotheses are accepted that say that one of the two varieties of Peanut will provide us the best agronomic yield and that at least one of the treatments will provide us the best relationship cost-benefit.